Reformulation of Commercial Court Authority Regulations Relation to the Arbitration Clause - Al-Anshori, Huzaimah; Handayani, Emi Puasa; Jha, Gautam Kumar (Universitas Negeri Semarang, 2024)
The issue of jurisdiction in dispute resolution within the Commercial Court arises when the contract designates an arbitration clause as the preferred mechanism for resolving disputes. In the contractual agreement between PT. Swadaya Graha and PT. Rayon Utama Makmur (RUM), the chosen forum for dispute resolution is stipulated to be the National Arbitration Board (BANI). However, concurrently, there is a proposal for dispute resolution within the Commercial Court framework concerning defaulted debt and receivable disputes in PKPU case number 45/Pdt.Sus-PKPU/2020/PN Niaga Smg. This has engendered a legal debate centring on the application of the